Time in embodied interaction synchronicity and sequentiality of multimodal resources - Deppermann, Arnulf; Streeck, Jürgen (Pragmatics & beyond., 2018)
"This is the first book dedicated to the study of the complexities that arise in embodied interaction from the multiplicity of time-scales on which its component processes unfold. It shows in microscopic detail how people synchronize and sequence modal resources such as talk, gaze, gesture, and object-manipulation to accomplish social actions. The studies show that each of these resources has its own temporal trajectory, affordances and restrictions, which enable and constrain the fine-grained work of bodily self-organization and interaction with others. Focusing on extended interactional time scales, some of the contributors investigate ways in which larger interactional episodes and relationships between actions are brought about and how actions build on shared interactional histories. The book makes a strong case for the use of video in the study of social interaction. It proposes an enlarged vision of Conversation Analysis that puts the body and its interactive temporalities center stage"--